2021
DOI: 10.3390/molecules26092818
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Evaluation of Late Season Peach Varieties (Prunus persica L.): Fruit Nutritional Quality and Phytochemicals

Abstract: Peaches are one of the most preferred seasonal fruits, and a reliable source of nutrients. They possess biologically active substances that largely differ among varieties. Hence, revealing the potential of several late season peaches is of present interest. Three commonly consumed varieties (“Flat Queen”; “Evmolpiya”; “Morsiani 90”) were studied in terms of nutritive and phytochemical content, as well as antioxidant activity with the use of reliable spectrophotometric and High Performance Liquid Chromatographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 112 publications
3
15
0
Order By: Relevance
“…In accordance with a previous HPLC-DAD analysis of peach varieties [45,55], two monosaccharides (glucose and fructose) and one disaccharide (sucrose) were present in polar fraction I (Table 1). Sucrose, while prevalent in all samples, had the highest content in the "Laskava" variety.…”
Section: Gas Chromatography-mass Spectrometry (Gc-ms) Profiling Of Polar and Nonpolar Compounds Of Analyzed Peach Samplessupporting
confidence: 90%
See 2 more Smart Citations
“…In accordance with a previous HPLC-DAD analysis of peach varieties [45,55], two monosaccharides (glucose and fructose) and one disaccharide (sucrose) were present in polar fraction I (Table 1). Sucrose, while prevalent in all samples, had the highest content in the "Laskava" variety.…”
Section: Gas Chromatography-mass Spectrometry (Gc-ms) Profiling Of Polar and Nonpolar Compounds Of Analyzed Peach Samplessupporting
confidence: 90%
“…Polyphenols and amino acids are also substrates for the phenylpropanoid and lignin pathways during stone hardening [ 59 ]. Previous analysis of phenolic acids in the investigated peach varieties (HPLC-DAD) also revealed that chlorogenic acid was the major phenolic compound [ 45 , 55 ]. Similarly, other studies also reported that chlorogenic acid was one of the main phenolic acids in different peach varieties [ 41 , 60 , 61 , 62 , 63 , 64 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The calculation method was used to determine the nutritional data. Supplier specifications for each of the ingredients (nuts, fruit, oil) were used to calculate the nutritional value of the finished products per 100 g. Information about the “Evmolpiya” peach was retrieved from previous research [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…The “Evmolpiya” peach is a native Bulgarian late-season variety with health-promoting properties. It has a rich total phenolic content and total flavonoid content [ 11 ]. Moreover, its extracts showed potency to inhibit certain enzymes (α-glucosidase, lipase, α-amylase, and acetylcholinesterase) [ 12 ].…”
Section: Introductionmentioning
confidence: 99%